A DESCRIPTIVE STUDY ON THE ENGLISH TEACHING-LEARNING PROCESS AT THE THIRD YEAR OF SMPN 1 BOYOLALI IN 2007/2008 ACADEMIC YEAR - KUSUMANINGATI, ANDIETA ASFRICO (2007)
This study attempts to describe the method used in English teaching- learning process, to describe the problem faced by the teacher in English teaching, and to describe the problem faced by the student in English learning at SMPN 1 Boyolali in 2007/2008 Academic Year. The writer limits the research for the third year students. This research belongs to qualitative research which employs descriptive data. The data are derived from event, informants, and documents. There are three techniques in collecting data, namely: Interview, observation, and documentation. Based on the data analysis, the conclusions are as follows: (1) the method used by teacher is Natural Approach (NA) and Communicative Language Teaching (CLT), (2) the problems faced by the teacher are the students cannot memorize the vocabulary well, so teacher must teach the vocabulary repeatedly. It makes the teacher must an ticipate the time allotment , In listening class, the students got the minimum score, and (3) t he students have some problems in listening class. Vocabulary and accents have been the common problem for the students.